Design and motion control scheme of a new stationary trainer to perform lower limb rehabilitation therapies on hip and knee joints. (2nd February 2022) - Sunilkumar, Parvathi; Mohan, Santhakumar; Mohanta, Jayant Kumar; Wenger, Philippe; Rybak, Larisa
Limb disability is one of the serious problems and rehabilitation of lower limb requires an assistive force to the patient. A new design for stationary trainer for performing rehabilitation therapies for lower limb at the knee as well as hip joints in the sitting/lying positions is presented in this article. A passive orthosis (similar to an exoskeleton) is suggested in this system to provide a support to lower limb of the patient. The suggested mechanism also comprises of an active Cartesian manipulator based upon a spatial three parallel prismatic–revolute–revolute–revolute kinematic arrangement to perform the required limb therapeutic motions in the transverse/horizontal/lateral and sagittal/longitudinal plane. Numerically, the usefulness of the designed stationary trainer is confirmed using computer-based simulations along with a motion control scheme by performing various clinically suggested therapeutic motion tracking (passive range of motions) tasks. The article demonstrates the accomplishment of the control scheme for various training procedures of the lower limb.